Workplace Loneliness and OCB: The Mediation Role of Affective Commitment - Ghista Dilla; Yulihardi (Yayasan Education Al Aqsho Modern, 2022)
This study aims to determine whether loneliness at work and OCB affect the Mediation Role of Affective Commitment. The location of this research was conducted at PT. Green Planet Indonesia branch Pekanbaru, Riau. While the time of the study was carried out from April to June 2021. The source of this research data is the respondent PT. Green Planet Indonesia. With 50 respondents as the research sample. The data analysis used in this paper is PLS Structural Equation Modeling (SEM) which is operated through the SmartPLS program. The results of this paper indicate that Workplace Loneliness has a negative and significant effect on Organizational Citizenship Behavior on employees at a private company PT. Green Planet Indonesia. Workplace Loneliness has a negative and significant effect on Affective Commitment to employees at a private company PT. Green Planet Indonesia. Affective commitment has a positive and significant effect on Organizational Citizenship Behavior on employees at a private company PT. Green Planet Indonesia. Affective commitment is not able to mediate workplace loneliness on Organizational Citizenship Behavior on employees at a private company PT. Green Planet Indonesia.